Potencial alelopático de Gmelina arborea (Verbenaceae) - Ramírez, Sandra (Universidad de Costa Rica, 1994)
The allelopathic potential of Gmelina arborea was tested on tomato. Seeds were placed under indirect natural light on Petri dishes (four replications, 20 seeds each) with absorbent paper. Three solutions were added: water, and 0.2 and 0.4 g/mI of mature leaves collected from three two year-old trees. The experiment was repeated under more intense light. The same solutions were added to pots with a mixture of soil and sat1d (four replications, ten plants each). There was a negative effect of the leaf extracts on germination (especially under low light), growth and total biomass (at least a 9.1,33.3 and 62.9% reduction, respectively). Roots were proportionately more affected